Globalizing Homeopathic Education: Convergence with WHO-GTM Strategy 2025-2034 (Homoeopathy for All, 2025)
The WHO Global Traditional Medicine (GTM) Strategy 2025–2034 emphasizes the need for culturally sensitive, regulated education across Traditional Medicine systems, including homoeopathy. Despite its global presence in over 100 countries, homoeopathy lacks consistent educational standards, underscoring the urgency for internationally aligned benchmarks. This paper advocates for the establishment of global educational guidelines to enhance quality, regulatory integration, and clinical credibility. It further proposes an interdisciplinary curriculum blending Hahnemannian philosophy with knowledge from Ayurveda, Yoga, Anthroposophy, and Naturopathy, along with nutrition and mind–body therapies. Active engagement of member states is essential to embed homoeopathy in health policies and academic dialogues. Emphasizing sustainability and local relevance, the paper highlights the need to align homoeopathic education with ecological, cultural, and biomedical realities. Finally, it positions India to take global leadership through innovation, collaboration, and academic excellence in homoeopathy.
Keywords: World Health Organization (WHO); traditional; medicine; Global